Digital learning resources and student success: Analyzing engagement and academic performance (Journal of Applied Learning and Teaching, 2025)
This study examines the impact of student engagement with digital learning resources – specifically sustained, timely, and distributed interactions with Learning Management Systems (LMS), e-textbooks, and digital study guides – on academic achievement outcomes in higher education. Using multiple regression analysis on data from 1,591 undergraduate students, the research identifies LMS engagement as a significant predictor of academic success, with specific behaviors such as prompt and consistent access strongly associated with academic performance. In contrast, e-textbooks and study guides play a more supplementary role. By incorporating confounding variables like age, gender, and academic mileage, the study offers a nuanced understanding of these relationships, underscoring the importance of an integrated approach to enhancing student engagement and learning outcomes.